Inside out - Poehler, Amy.; Smith, Phyllis; Kind, Richard; Hader, Bill.; Black, Lewis; Carmen, Story By Pete Docter & Ronnie del.; D, Screenplay By Meg LeFauve & Josh Cooley And Pete.; Hader, Additional Dialogue By Amy Poehler & Bill. ([S.l.] : Walt Disney Studios, 2015)
When 11-year-old Riley moves to a new city, her Emotions team up to help her through the transition. Joy, Fear, Anger, Disgust and Sadness work together, but when Joy and Sadness get lost, they must journey through unfamiliar places to get back home.
Starring Amy Poehler, Phyllis Smith, Richard Kind, Bill Hader, Lewis Black.
PG (Parental Guidance Suggested)
Blu-ray, AC-3, Animated, Color, Dolby, DTS Surround Sound, NTSC, Subtitled, Widescreen, Digital_copy.